Paediatric pneumonia in high-income countries: Defining and recognising cases at increased risk of severe disease. (September 2021) - Haggie, Stuart; Selvadurai, Hiran; Gunasekera, Hasantha; Fitzgerald, Dominic A.
Abstract: World Health Organisation definitions of pneumonia severity are routinely used in research. In high income health care settings with high rates of pneumococcal vaccination and low rates of mortality, malnutrition and HIV infection, these definitions are less applicable. National guidelines from leading thoracic and infectious disease societies describe 'severe pneumonia' according to criteria derived from expert consensus rather than a robust evidence base. Contemporary cohort studies have used clinical outcomes such as intensive care therapy or invasive procedures for complicated pneumonia, to define severe disease. Describing severe pneumonia in such clinically relevant terms facilitates the identification of risk factors associated with worsened disease and the subsequently increased morbidity, and need for tertiary level care. The early recognition of children at higher risk of severe pneumonia informs site of care decisions, antibiotic treatment decisions as well as guiding appropriate investigations. Younger age, malnutrition, comorbidities, tachypnoea, and hypoxia have been identified as important associations with 'severe pneumonia' by WHO definition. Most studies have been performed in low-middle income countries and whilst they provide some insight into those at risk of mortality or treatment failure, their generalisability to the high-income setting is limited. There is a need to determine more precise definitions and criteria for severe disease in well-resourced settings and to validate factors associated with intensive care admission or invasive procedures to enhance the early recognition of those at risk.